2013
DOI: 10.1155/2013/354965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biochar in Ameliorating Disturbed Soils and Sequestering Soil Carbon in Tropical Agricultural Production Systems

Abstract: Agricultural soils in the tropics have undergone significant declines in their native carbon stock through the long-term use of extractive farming practices. However, these soils have significant capacity to sequester CO2through the implementation of improved land management practices. This paper reviews the published and grey literature related to the influence of improved land management practices on soil carbon stock in the tropics. The review suggests that the implementation of improved land management pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…Nevertheless, important drivers for effective sequestration of SOC includes increased plant growth and productivity, increased net primary production, reduced rate of decomposition (Tieszen 2000), stabilization of carbon in the subsoil, organic amendment application to the soil (Powlson et al 2011), and biochar application (Sohi et al 2010;Verheijen et al 2009). Substantial increase in the total soil C pool with the application of biochar from various sources is well documented (Steiner 2010;Matovic 2011;Mekuria and Noble 2013;Jiang et al 2013;Woo 2013;Mbah et al 2017). For instance, Nigussie et al (2012) reported 0.71% C increment on a Nitosol in southeastern Ethiopia following the incorporation of maize stalk biochar (5 t ha −1 ) compared to a control (unamended plot).…”
Section: Options For Increasing Soil Organic Carbon Stock In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, important drivers for effective sequestration of SOC includes increased plant growth and productivity, increased net primary production, reduced rate of decomposition (Tieszen 2000), stabilization of carbon in the subsoil, organic amendment application to the soil (Powlson et al 2011), and biochar application (Sohi et al 2010;Verheijen et al 2009). Substantial increase in the total soil C pool with the application of biochar from various sources is well documented (Steiner 2010;Matovic 2011;Mekuria and Noble 2013;Jiang et al 2013;Woo 2013;Mbah et al 2017). For instance, Nigussie et al (2012) reported 0.71% C increment on a Nitosol in southeastern Ethiopia following the incorporation of maize stalk biochar (5 t ha −1 ) compared to a control (unamended plot).…”
Section: Options For Increasing Soil Organic Carbon Stock In Ethiopiamentioning
confidence: 99%
“…However, Lal (2016) submitted that biochar impact on soil C dynamics is dependent on biochars' properties in relation to the feedstock, pyrolysis, antecedent soil characteristics, and management systems. More so, Sohi et al (2009) as reported in Mekuria and Noble (2013) argued that the extent of the impact of biochar application on soil carbon sequestration (SCS) and agricultural production remains variable and not fully understood mainly due to the different soil processes (chemical, physical, and biological) and biophysical interactions occurring due to biochar application, which yearns for more critical study for clear understanding. Conservation tillage, cover crops, integrated soil fertility management (ISFM), irrigation, restoration of degraded soils, management of pasture lands, forest soils, stabilization of carbon in subsoil, and afforestation (see Lal 1998;Lal 2008b;Lal et al 2012) are among the recommended soil and crop management practices acting individually and collectively to improve the SOC pool in the terrestrial ecosystem.…”
Section: Options For Increasing Soil Organic Carbon Stock In Ethiopiamentioning
confidence: 99%
“…Biochar can be incorporated into soil for improving soil productivity, carbon sequestration and water retention (Novak et al, 2012). Boichar is not a compost material, rather, it is a catalyst of soil microbial activity which augments soil chemical properties and enhances soil water storage capacity to increase crop productivity (Steiner et al, 2007., Lehmann & Joseph, 2015., Liu 2012., Mekuria et al, 2013and Akhter et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the short-term effects of biochar on plant growth and soil behavior reported from laboratory studies were not observed in the field emphasizing the need for long term field trials to help inform agronomic management decisions involving biochar (Jones et al, 2012). More so, adequate care should be taken on the amount and type of biochar added to the soil for restoring degraded soils (Mekuria and Noble, 2012).…”
Section: Introductionmentioning
confidence: 99%